2015
DOI: 10.1097/ajp.0000000000000190
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Lumbar Spine Functional Movement in Low Back Pain

Abstract: This study provide support for the utility of this device for quantifying movement impairments in individuals with fairly low levels of LBP and general functional limitations. The results show that velocity measurements rather than ROM show the greatest differences in individuals with LBP compared with asymptomatic participants. Impaired lumbar and pelvis movement was correlated to the individuals with LBP's degree of anxiety, fear, and catastrophizing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
53
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 31 publications
3
53
0
3
Order By: Relevance
“…FA should logically be associated with decreased physical performance on tasks that might provoke pain. Some previous studies in various chronic pain populations have found associations between FA‐related measures and performance measures, including lifting, range of motion, walking, gait speed, and strength production . The present study evaluated the association between FACS scores and “zero” scores on the PILE, an objective lifting task.…”
Section: Discussionmentioning
confidence: 95%
“…FA should logically be associated with decreased physical performance on tasks that might provoke pain. Some previous studies in various chronic pain populations have found associations between FA‐related measures and performance measures, including lifting, range of motion, walking, gait speed, and strength production . The present study evaluated the association between FACS scores and “zero” scores on the PILE, an objective lifting task.…”
Section: Discussionmentioning
confidence: 95%
“…A qualidade de vida comprometida nos domínios físico, psicoló-gico e relações sociais assemelham-se a outros dados, revelando que as dimensões físicas e relações sociais podem ser preditores da ocorrência e expressão do sintoma álgico pós-cirurgia (18) . Com relação ao medo do movimento, este é um fator de risco para o aumento da dor, incapacidade e redução da função fí-sica em pacientes após cirurgia de coluna (19) . Neste estudo foi verificado um alto grau de cinesiofobia, concordante ao estudo sueco (17) , que avaliou 80 pacientes com radiculopatia lombar tratados cirurgicamente e que responderam à Escala Tampa de Cinesiofobia, obtendo uma média de 39,1 ± 8,45.…”
Section: Discussionunclassified
“…28 However, these findings are contradictory to those of earlier studies reporting associations between physical ability and fear avoidance beliefs. 9,11,29 In one study, Geisser et al observed a significant correlation between pain-related fear and decreased lumbar flexion among participants with chronic LBP. 9 Vaisy et al reported that ROM and angular velocity were associated with psychological characteristics, including fear of movement.…”
Section: Discussionmentioning
confidence: 99%
“…9 Vaisy et al reported that ROM and angular velocity were associated with psychological characteristics, including fear of movement. 11 Grotle et al found that fear avoidance beliefs were significantly related to disability after controlling for sociodemographic, pain-related and clinical variables and excluding distress variables. 30 Another study found that a combination of psychological factors, including fear avoidance beliefs, anxiety and pain catastrophising, determined functional disability in adults with chronic LBP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation